AN ANALYSIS OF THE USE OF ENGLISH IN BUSINESS CORRESPONDENCE IN MEDAN AND ITS IMPACT ON PROFESSIONAL COMMUNICATION EFFECTIVENESS IN THE ERA OF DIGITAL GLOBALIZATION - Emmy Erwina; Bima Prana Chitra; Lisna Sari Siregar; Widelya Shafa April; Winanda Salvira (Vernacular: Linguistics, Literature, Communication and Culture Journal, 2025)
The increasing use of English in international business has made effective written communication an essential component of professional interaction in the era of digital globalization. This study aimed to analyze the use of English in business correspondence among selected companies in Medan and examine its impact on professional communication effectiveness. A qualitative descriptive research design was employed to investigate eight authentic business correspondence documents collected from companies operating in various business sectors. The data were analyzed using thematic analysis focusing on five linguistic aspects: grammatical accuracy, vocabulary use, politeness strategies, organizational structure, and message clarity. The findings revealed that most business correspondence demonstrated good grammatical accuracy, appropriate business vocabulary, complete organizational structure, and consistent use of positive politeness strategies. Five of the eight documents were categorized as highly effective, while two were classified as effective and one as moderately effective. Although minor grammatical errors were identified in several documents, these inaccuracies did not significantly affect the overall communicative purpose because the messages remained clear and professionally organized. The study concludes that communication effectiveness in English business correspondence is influenced not only by grammatical competence but also by appropriate vocabulary, coherent organization, politeness strategies, and message clarity. These findings contribute to the development of Applied Linguistics and English for Specific Purposes (ESP) by providing practical insights into authentic workplace communication and offering recommendations for improving Business English competence in professional settings.